Sistem Informasi Penjualan Barang Berbasis Website Dengan Algoritma Collaborative Filtering Di CV. Anjas Konveksi Bekasi - Akmal Maulfi Anwar; Andy Achmad Hendharsetiawan (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
CV. Anjas Group Indonesia and its subsidiary, Anjas Konveksi, are business entities that focus on the production and sale of clothing such as t-shirts, shirts, jackets, and the like. The availability of various products often confuses some customers in making choices that suit their desires. To overcome this, a recommendation system is needed that can help customers find products that match their preferences, facilitating the buying process. In this research, the Item Based Collaborative Filtering approach is used, which aims to find similarities between the purchasing patterns of one product and another (item similarity). The system will look for similarity values between products based on cosine similarity. After getting the rating value between products, the Item Based Collaborative Filtering method will be used to provide recommendations to customers according to their preferences.